2007
DOI: 10.1111/j.1743-6109.2007.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Female Sexual Function and Dysfunction During Pregnancy

Abstract: Introduction Although women may undergo changes in sexual function during pregnancy, there are limited studies correlating possible sexual function changes to androgen blood levels during the pregnancy. Aim To search for a possible correlation, we performed a cross-sectional observational study to assess sexual function scores and androgen blood levels of women during pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
89
2
22

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 39 publications
12
89
2
22
Order By: Relevance
“…Main factors which may lead to sexual dysfunction during pregnancy are physical and hormonal changes that may cause perceived loss of attractiveness, diminished self-esteem due to low body image and other psychological factors. [18] The prevalence of FSD among pregnant women was reported between 50-80% in the literature. [9,12,15,19] In Turkey, epidemiological studies revealed a much higher rate of FSD during pregnancy as 80-90%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Main factors which may lead to sexual dysfunction during pregnancy are physical and hormonal changes that may cause perceived loss of attractiveness, diminished self-esteem due to low body image and other psychological factors. [18] The prevalence of FSD among pregnant women was reported between 50-80% in the literature. [9,12,15,19] In Turkey, epidemiological studies revealed a much higher rate of FSD during pregnancy as 80-90%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrary, some studies demonstrated a relative increase in sexual functions during second trimester when compared to the first and third trimesters. [11,12,18] The reasons of increased sexual dysfunction in the first trimester were related to increased fatigue due to nausea, vomiting and inability to comply with this new period. [13] Cessation of those complaints, less fear of miscarriage and increased vascular congestion may contribute to decreased rate of FSD in the second trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de diversos trabalhos analisarem a função sexual durante a gravidez 3,4,[7][8][9][10][11]19,25 , não encontramos estudos que a correlacionassem com a qualidade de vida em gestantes saudáveis. Sabe-se que a função sexual passa por mudanças na gestação, ocorrendo o aumento de sintomas de disfunção sexual, como a diminuição de desejo e a dispareunia nesse período 9,[11][12][13] .…”
Section: Discussionunclassified
“…Somente o fato de tomar conhecimento da gravidez, logo nas primeiras semanas, parece afetar a atividade sexual feminina, diminuindo o número de coitos 2 . Estudos mostram que nos mais diversos contextos socioeconômico e cultural as mulheres podem apresentar dificuldades com desejo, excitação, orgasmo, lubrificação, além de insatisfação sexual e dispareunia na gravidez [2][3][4][5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Introductionunclassified